2020
DOI: 10.1177/1533033820920967
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulatory Network Analysis of MiR-139-3p, a New Potential Serum Biomarker for Esophageal Squamous Cell Carcinoma Based on Bioinformatics Analysis

Abstract: Background: In recent studies, microRNAs have been demonstrated as stable detectable biomarkers in blood for cancer. In addition, computer-aided biomarker discovery has now become an attractive paradigm for precision diagnosis. Methods: In this study, we identified and evaluated miR-139-3p as a biomarker for screening of esophageal squamous cell carcinoma using the Cancer Genome Atlas and Gene Expression Omnibus database analyses. We identified possible miR-139-3p target genes through the predicted database an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…MiR-139-3p is a candidate serum biomarker for predicting the prognosis of ESCC. Previous study showed that FCGR2A could be mediated by miR-139-3p at the posttranscriptional level (25). GNGT1 can predict the response to platinum-based chemotherapy drugs (26).…”
Section: Discussionmentioning
confidence: 98%
“…MiR-139-3p is a candidate serum biomarker for predicting the prognosis of ESCC. Previous study showed that FCGR2A could be mediated by miR-139-3p at the posttranscriptional level (25). GNGT1 can predict the response to platinum-based chemotherapy drugs (26).…”
Section: Discussionmentioning
confidence: 98%
“…A tumor suppressor role has also been described in bladder cancer [ 109 ], CRC [ 110 ], glioblastoma multiforme [ 111 ], BC [ 45 ], and HCC [ 112 ]. Additionally, miR-139-3p is downregulated in serum in patients with esophagal squamous cell cancer (SCC), highlighting its potential as a serum biomarker [ 113 ]. miR-139-5p is a regulator of osteoblast differentiation and apoptosis by targeting ELK1 and ODSM [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al has been demonstrated that lncRNA TP73-AS1 reducedmiR-139-3p to promote retinoblastoma cell proliferation [ 24 ]. In addition, miR-139-3p was predicted to be acted as a tumor suppressor in ESCC [ 25 ]. Interestingly, miR-139-3p was the target of BCAR4 in our study through online bio-prediction site.…”
Section: Introductionmentioning
confidence: 99%